1998
DOI: 10.1021/ja982217n
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Zinc(II)-Dithiocarbamate-Accelerated Vulcanization Uncovered; Theoretical and Experimental Evidence

Abstract: The mechanism of cross-link formation in sulfur vulcanization mediated by bis(dimethyldithiocarbamato)zinc(II), ZDMC, has been uncovered, utilizing a combination of Density-Functional calculations and model experiments. These studies have revealed that, in a three-stage process, ZDMC exhibits a unique combination of catalytic activity:  (1) It mediates the reaction between sulfur and rubber. This is achieved by incorporating sulfur atoms in the zinc-dithiocarbamate ring and inducing their insertion into an all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(117 citation statements)
references
References 25 publications
4
111
0
2
Order By: Relevance
“…Elemental analysis data and melting point are presented in TABLE (1). Elemental analysis data shows that there are no significant difference between experimental and theoritical value which indicates that all compounds are pure.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Elemental analysis data and melting point are presented in TABLE (1). Elemental analysis data shows that there are no significant difference between experimental and theoritical value which indicates that all compounds are pure.…”
Section: Resultsmentioning
confidence: 96%
“…Dithiocarbamate complexes are important in rubber industry as vulcanization accelerator [1] and in agriculture sector as fungicide agent and pesticide [2]. Current research have shown that many dithiocarbamate complexes show positive response towards anti-microb and anti-cancer activities through in-vitro [3][4].…”
Section: Introductionmentioning
confidence: 99%
“…[1~3] 及生物活性 [4~6] , 同时还可 用作硫化剂 [7] 、 光引发剂 [8] 等. 该类化合物常用的合成方 法是: 在强碱性条件下, 伯胺或仲胺与二硫化碳反应生 成对应的氨基二硫代甲酸盐, 再与卤代烷反应, 生成氨 基二硫代甲酸酯, 但由于需要在强碱性条件反应, 使反 应底物中不能含有对碱敏感的基团, 同时存在中间体需 要分离, 反应时间较长等缺点 [9] .…”
Section: 二硫代氨基甲酸酯衍生物是一类应用广泛的化合 物 具有较好的生理活性unclassified
“…However, ZnO release into the environment that occurs during production, disposal and recycling of rubber products, which is in soluble zinc compounds is classified as ecotoxic to aquatic organisms [5,7,[9][10]. Moreover, usage of ZnO is also associated with a problem related to mold fouling that occurs during rubber manufacturing [9,[13][14]. There is evidence that during vulcanization, a considerable amount of ZnO is consumed and transformed into zinc sulfide (ZnS), which is a by-product of the vulcanization reactions.…”
Section: Introductionmentioning
confidence: 99%